The efficacy of using established physical testing and a novel movement coordination test battery for talent identification into a selective entry school-based sports academy - Berry, J.; Vallance, B.; Clark, D. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Physiological and anthropometric testing has provided the metrics most widely adopted to inform the talent identification process (Vaeyens, Lenoir, Williams, & Philippaerts, 2008). Currently, there is a lack of research to inform this important process at younger age levels for entry into talented athlete pathways. A relatively new movement coordination test battery has been proposed as a useful talent identification tool in younger athletes. The KorperKoordinations Test Fur Kinder (KTK) is a non-sport specific battery that includes tasks of balancing, hoping, and jumping (Vandorpe et al, 2012). The use of established physical test protocols along with the addition of the novel KTK movement coordination test may provide a more robust information set to guide the talent identiifcation process. The use of performance metrics to aid the selection process is relatively new at the academy and selection has relied primarily on the `coaches eye` in the past. The purpose of this study was to 1) investigate if the physical test battery can systematically identify those prospective studentathletes that are subsequently selected into the sports academy, and 2) investigate if a general test of movement coordination (KTK) can systematically identify those prospective student-athletes also. Methods: Participants were 102 male (11-12yrs) prospective student-athletes with 37 of those subsequently identified as talented and offered a place at the academy. The physical test battery consisted of height and weight, vertical jump, and a 20m speed. The movement coordination test battery consisted of four discrete tasks that were timed and/or scored. The tasks are 1) walking backwards on a balance beam (x3 widths), 2) single leg hoping over foam blocks progressing in height with each successful attempt, 3) sideways jumping over a centre divider, and 4) manipulation of two small support platforms to move across the floor. Results: ANOVA revealed a significant main effect for group with 20m speed, hopping for height, sideways jumping, and platforms superior for the academy group. Positive or neutral data trends were exhibited across the remaining variables for height, weight, vertical jump, and balance. Discussion: The results indicate 20m speed and the inclusion of a general test of movement coordination appears to be a useful addition to a talent identification test battery for Sport Academy selection at the primary-to-secondary school transition point.